Eficiência de corte de instrumentos rotatórios de níquel-titânio para alargamento cervical de canais radiculares : análise em estereomicroscopia, perfilometria e microtomografia computadorizada - Morgental, Renata Dornelles (2012)
This study aimed to: evaluate, using different methods and substrates, the cutting efficiency of nickel-titanium rotary instruments for coronal flaring; investigate the influence of rotational speed and number of uses on the cutting efficiency of such instruments; observe the presence of surface defects. First, bovine dentin blocks (n=20) and acrylic blocks (n=20) were made, as substrate for evaluating the performance of the following instruments: BR0 BioRaCe (BR), HyFlex CM 1 (HY), ProFile OS #2 (PF) and ProTaper Sx (PT). Each instrument worked sideward for 60 seconds, mounted on a testing platform. The instruments were used at two rotational speeds (250 and 500 rpm) up to 5 times. On the first stage, those blocks were observed under a stereomicroscope and the notches created by the instruments were measured.Area and length were used as parameters to assess cutting efficiency. Data were statistically analyzed with significance level set at 5%. HY and PF were the most and least efficient instruments (P<0.05), respectively. Against acrylic, with greater speed, significant increase in area and length was observed for all instruments. Against dentin, there was significant increase in area for HY and PT and in length for BR, HY and PT. Regarding the number of uses, there was no cutting efficiency loss against acrylic. On dentin, however, PF and PT instruments were significantly less efficient after the fourth and fifth use (shorter length). Strong correlation was found between the results on acrylic and dentin for all brands. On the second stage, two new parameters were used to assess cutting efficiency.Dentin blocks were evaluated under a profilometer to determine the maximum cutting depth of the notches. Half of them were also investigated by microcomputed tomography (micro-CT) to check the volume of extracted dentin. Data were statistically analyzed with significance level set at 5%. Again, HY and PF were the most and least efficient instruments (P<0.05). Speed increase significantly improved maximum cutting depth (BR, HY and PT) and volume of extracted dentin (HY and PF). BR and PT instruments lost their cutting efficiency after repeated use (depth and volume) as well as HY (volume).Positive correlation coefficients were found between profilometry and micro-CT results. Finally, instruments were examined under scanning electron microscopy (SEM) for the presence of surface defects. Most instruments had blunt cutting edges after use, but there was no relevant deformation or fracture. In conclusion, stereomicroscopy showed similar results to wellrecognized methods (profilometry and micro-CT), evidencing HY superiority. Rotational speed and number of uses had a positive and negative influence, respectively, on the cutting efficiency of nickel-titanium coronal flaring instruments